Chapter 11 Dogmas of Superficiality The Episteme of Humanism in Writings by Taiwanese Historians Huang Chun-chieh,Wong Young-tsu, and Hu Chang-Tze - Timme Kragh, Ulrich (National Taiwan University Press, Vandenhoeck & Ruprecht V&R Unipress, 2015)
The article critically analyzes the characterization of Asian traditions as 'humanism' as presented in the writings by three Chinese historians.